2015
DOI: 10.1007/s11743-015-1720-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chain Length on the Micellization, Antibacterial, DPPC Interaction and Antioxidant Activities of l‐3,4‐Dihydroxyphenylalanine (l‐DOPA) Esters

Abstract: L-DOPA (L-3,4-dihydroxyphenylalanine) has been widely used as a drug in the clinical treatment of Parkinson's disease. In this report, the systematic study of the effect of chain length on the critical micelle concentration (CMC), antibacterial and antioxidant activity of esters derived from the aromatic amino acid L-3,4-dihydroxyphenylalanine as surfactants are accounted for the first time. The antibacterial activity displayed a cut-off effect at C 12 with respect to both gram positive and gram negative bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Lipophilicity is also known to influence the biological activity of various compounds [11,12]. Turos et al reported that increasing alkyl chain length from methyl to butyl in alkylaryl disulfide system enhances the anti-bacterial properties of these compounds [13].…”
Section: Introductionmentioning
confidence: 99%
“…Lipophilicity is also known to influence the biological activity of various compounds [11,12]. Turos et al reported that increasing alkyl chain length from methyl to butyl in alkylaryl disulfide system enhances the anti-bacterial properties of these compounds [13].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has been dealing with the synthesis, physicochemical and biological properties of O-alkyl esters of aromatic and cyclic amino acids [14][15][16][17][18]. In this study, a series of O-alkyl ester of methionine and their hydrochloride derivatives were synthesised and their physicochemical properties were investigated.…”
Section: Introductionmentioning
confidence: 99%